Networks of Volatility Spillovers among Stock Markets - Eduard Baumöhl; Ev en Kocenda; Stefan Lyócsa; Tomás Vyrost (Center for Economic Studies and ifo Institute (CESifo), 2017)
In our network analysis of 40 developed, emerging and frontier stock markets during 2006–2014, we describe and model volatility spillovers during global financial crisis and tranquil periods. The resulting market interconnectedness is depicted by fitting a spatial model incorporating several exogenous characteristics. We show significant temporal proximity effects between markets and somewhat weaker temporal effects with regard to the US equity market – volatility spillovers decrease when markets are characterized by greater temporal proximity. Volatility spillovers also present a high degree of interconnectedness. Our results also link spillovers of escalating magnitude with increasing market size, market liquidity and economic openness.
Keywords: C31; C58; F01; G01; G15; 330; volatility spillovers; stock markets; shock transmission; Granger causality network; spatial regression; financial crisis